1993
DOI: 10.5739/isfp.1993.677
|View full text |Cite
|
Sign up to set email alerts
|

Experimental identification and modelling of flow and torque losses in gerotor hydraulic motors

Abstract: The experimental identification and graphical verification of flow-and torque-loss and coefficient of efficiency in the work space is needed for designers, to set up the static performance specifications and diagnosis of hydraulic pumps and motors. This paper presents and proposes an experimental based method for identification and modelling of flowand torque-loss for hydraulic motors. The method is based on least-square approximation technique. As an example, the experimental results and modelling results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In 1970, the original author, having conducted hundreds of tests on both pumps and motors, of both fixed and variable displacement types, prepared a technical paper [1] on an empirical method for determining the displacement of positive displacement pumps and motors. This paper has been cited by a number of other authors, notably, Post [2], Conrad et al [3], and Ivantysyn and Ivantysynova [4]. Anecdotally, the method has been adopted by an unknown number of individuals working in hydraulic laboratories around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1970, the original author, having conducted hundreds of tests on both pumps and motors, of both fixed and variable displacement types, prepared a technical paper [1] on an empirical method for determining the displacement of positive displacement pumps and motors. This paper has been cited by a number of other authors, notably, Post [2], Conrad et al [3], and Ivantysyn and Ivantysynova [4]. Anecdotally, the method has been adopted by an unknown number of individuals working in hydraulic laboratories around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Post [2] also compared three methods for the determination of the displacement of a hydraulic machine; after his study, he concluded that this method was preferable to the existing ISO method. Conrad et al [3] preferred the use of this method for the validation of their mathematical model of the flow and torque loss of a pump. According to Myszkowski [8] and Czyński [9], the work of Balawender from 1988 detailed a careful analysis of the energy losses in hydraulic equipment using an energy balance approach.…”
Section: Introductionmentioning
confidence: 99%
“…The total efficiency is very much related to losses. Experimental and torque losses in gerotor were investigated in case of hydrostatic machines which represent complex fluid dynamic systems due to intricate and partially unknown dynamics [8]. Some losses are related to tribological behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More sophisticated methods like the one presented by Eggers, et al [6] were used to describe a mathematical interpolation procedure called POLYMOD, which was used for developing a torque and flow model based on a polynomial fit of experimental test data. Similarly, Conrad et al [7] developed a loss model where the flow losses could be obtained from fitting experimental data to a line. Whether the aim is to obtain a complete flow model or simply for determining the volumetric displacement of the pump or motor, a set of experimental data points is required.…”
Section: Introductionmentioning
confidence: 99%